Behavior of CFRP-strengthened RC beams with circular web openings in shear zones: Numerical study. (July 2022) - Özkılıç, Yasin Onuralp; Aksoylu, Ceyhun; yazman, Şakir; Gemi, Lokman; Arslan, Musa Hakan
Abstract: In practice, especially the basement floor beams are drilled and damaged by the users. In some cases, this damage to the beams can be significant for the load-bearing element and the whole structure. In this study, the behavior of reinforced concrete beams with circular openings and the failure types resulting from strengthening these beams with CFRP are parametrically investigated. The diameter of the opening/beam height ratio (D/H), concrete compressive strength, stirrup spacing, the position of the opening to the beam support, the type of CFRP application, CFRP ply orientation, and the number of CFRP layers were selected as parameters. Numerical models were verified using 9 specimens having different circular openings with/without CFRP strengthening and the analyses of 95 numerical models with the selected parameters were carried out utilizing the finite element program, ABAQUS. The ultimate load capacity, ductility, stiffness, energy dissipation capacity and failure modes of the beams were determined. As a result of the study, it was observed that there was no significant loss in ductility for the beams with D/H ≤ 0.3 and the number of CFRP layer and type of application did not have a significant effect on D/H ≤ 0.44. However, for the beams with D/H > 0.64, the CFRP application that completely surrounds openings should be preferred instead of partial CFRP strengthening. In addition, the concrete strength is an effective parameter for the beams with D/H ≤ 0.44. The effect of the stirrup spacings in the beam on the ductile behavior was also limited with the increase in the hole diameter. The number of CFRP layers should theoretically be 4 for an effective strengthening in beams with D/H > 0.44. Finally, U wrapping is recommended instead of using full wrapping. It has been seen that the location and diameter of the hole are very important parameters in the failure type of the beam.